DETERMINATION OF CAPITAL INVESTMENT TRENDS OF INDUSTRIAL PRODUCTION IN THE CONDITIONS OF UNCERTAINTY, THREATS AND RISKS - TULCHYNSKA, Svitlana; KOZHEMIACHENKO, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the trends of changes in capital investment in industry and determines the trends of further investment in conditions of uncertainty, threats and risks. Capital investments in industry for 2010-2022 were analyzed. It was determined that the general level of capital investments in the industry of Ukraine in the period 2010-2022 increased, with the exception of 2020. The number of industrial enterprises that introduced innovations for the period 2013-2020 was analyzed as a percentage of the total number. During the period 2013-2016, there was an increase in enterprises that implemented innovative processes in their activities, in 2017 and 2019, there was a slight decrease in innovative activity compared to the previous period. It is substantiated that the main vectors of development among science-intensive types of industry and mechanical engineering should become: the development of the aviation industry, rocket and space technology, the production of new types of rolling stock, the development of the energy industry, the production of electronic equipment and the modernization of the defense complex. To ensure the security and competitiveness of the state, it is necessary to develop modern types of weapons and military equipment. Among the priorities: radar systems, high-precision weapons and means of their destruction, missile complexes of various ranges. In order to maintain competitive positions in the field of mining and metallurgical production, it is necessary to develop directions for the diversification of production, optimization of the structure according to the nomenclature range, development of new types of goods and services on the basis of existing production capacities. It is necessary to develop and attract new, more effective methods of development of natural reserves of mineral raw materials.